Strategi Pengelolaan Objek Wisata Mangrove Pandansari Sebagai Salah Satu Pendapatan Asli Daerah Kabupaten Brebes - Eldo, Dwian Hartomi Akta Padma; Prabowo, Azra Fadila (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2020)
This paper aims to see how the local government of Brebes Regency manages the Mangrove Sari tourist sites by using the Planning, Organizing, Actuating, Controlling (POAC). The research method in this paper uses a descriptive qualitative approach. The author conducted interviews directly with stakeholders such as the Brebes local government and also the community that manages the Sari Mangrove tourism site. The aim is to see how the strategies carried out by local governments and also the practice in the field whether it is going according to plan or not. The results showed that the local government has not been maximized in optimizing Pandansari Tourism Objects as one of the original revenue of the Brebes Regency. In addition the local government in this case the Department of Tourism and Culture is still not effective in carrying out coordination and direction for future development with the management of the tourism object in this case the local community group. Therefore, some input that can be given is to improve coordination with the management of attractions and to draft long-term and short-term development plans for Pandansari Mangrove Tourism Objects.